Study on Cryopreservation of Human Hepatoma Hep-G2 Cell - Yao Lan; Liang Wei; Liu Baolin (Zhileng xuebao)
It is well known that the type and concentration of cryoprotectant (CPAs) exerts a significant influence on the survival rate of cells following cryopreservation. The optimal cryoprotectant for human hepatoma Hep-G2 cell with slow cooling method was determined in the study. The Cells were frozen in Me2SO, glycerol, sucrose and trehalose at different concentration and combination, then stored in a ﹣80 ℃ freezer for one week. The survival rate was assessed by trypan blue dye exclusion test, MTT assay and 24 h attachment assay. The results suggested that 10% (v/v) Me2SO provide effective protection among Me2SO groups; 20% (v/v) glycerol provide effective protection among glycerol groups; when sugars were added, 5%Me2SO(v/v)+0.3mol/L trehalose provide effective protection than the other groups（P<0.05）. In conclusion, 5% Me2SO (v/v)+0.3mol/L trehalose was the presumptive optimal cryoprotectant for human hepatoma Hep-G2 cell during slow freezing.